Importance of Amplitude Stability and Spectral Purity of Produced Signals in a Quadrature Oscillator - Jerabek, J.; Sotner, R.; Herencsar, N.; Kartci, A. (IEEE, 2015)
This paper presents two solutions for an amplitude automatic gain control circuit implemented in a simple second-order quadrature oscillator based on the non-inverting band-pass filtering response and a block with positive feedback with controllable gain or intentional nonlinearity. The results regarding amplitude stability, total harmonic distortion, available tunability range, time required to obtain stable oscillations, etc. are discussed and both AGC solutions are compared. PSpice software was used for verification in simulations.
Keywords: Amplitude automatic gain control; diamond transistor; quadrature oscillator; total harmonic distortion; tuning; variable gain amplifier; Computer Science